Evaluation of cervical maturity by cervical collagen measurement using light-induced fluorescence (LIF) during pregnancy. Issue 11 (November 2020) - Zheng, Zheng; Di, Xiaodan; Wang, Lele; Zhang, Weijuan; Feng, Yan; Shi, Shao-Qing; Garfield, Robert E; Liu, Huishu
Objective: The study aimed to evaluate cervical ripening by measuring cervical collagen levels in non-pregnant women, women with a normal pregnancy, and postpartum women by light-induced fluorescence (LIF). Methods: Cervical collagen content in normal pregnant women (n = 165) at various times of gestation was measured by LIF with a collascope, which is specifically designed to measure fluorescence of collagen. Cervical LIF in non-pregnant women (n = 12) and postpartum women (n = 14) was also detected. The demographic characteristics of women at various times were recorded. The Bishop score at 40 to 41 gestational weeks (n = 37) before the onset of labor was analyzed. Results: Cervical LIF values progressively declined from the non-pregnant state to late gestation (R = −0.836) and reached their lowest levels during parturition and then increased at postpartum. LIF values and the Bishop score were significantly negatively correlated (R = −0.83). In patients with a Bishop score ≥6, the first stage of labor was shortened with a decrease in LIF values (R = 0.718). Conclusions: Cervical collagen levels as measured by LIF could be a useful method for evaluating cervical maturity.